Particle entrainment from gas‐solid fluidized beds: Conductive vs. dielectric fines - Fotovat, Farzam; Grace, John R.; Bi, Xiaotao T. (AIChE journal, 2017)
Conductive and non‐conductive fine powders were entrained by air at atmospheric temperature and pressure in a fluidization column of diameter 0.15 m made of stainless steel. Under equivalent operating conditions, entrainment of the conductive particles was markedly higher than for non‐conductive species. This finding cannot be explained by hydrodynamic factors. Examining the electrostatic interaction between touching particles reveals that dominance of the inter‐particle attractive forces hinders independent motion of non‐conductive particles in the freeboard. In addition, because of non‐uniform distribution of the electrical charges over the surface of dielectric particles, they are subject to stronger electrostatic forces than for particles made of conductive materials. © 2016 American Institute of Chemical Engineers AIChE J, 63: 1194–1202, 2017